Comprehensive summary: the role of PBX1 in development and cancers - Liu, Mingsheng; Xing, Yan; Tan, Jiufeng; Chen, Xiaoliang; Xue, Yaming; Qu, Licheng; Ma, Jianchao; Jin, Xuefei (Frontiers in Cell and Developmental Biology, 2024)
PBX1 is a transcription factor that can promote the occurrence of various tumors and play a regulatory role in tumor growth, metastasis, invasion, and drug resistance. Furthermore, a variant generated by fusion of E2A and PBX1, E2A-PBX1, has been found in 25% of patients with childhood acute lymphoblastic leukemia. Thus, PBX1 is a potential therapeutic target for many cancers. Here, we describe the structure of PBX1 and E2A-PBX1 as well as the molecular mechanisms whereby these proteins promote tumorigenesis to provide future research directions for developing new treatments. We show that PBX1 and E2A-PBX1 induce the development of highly malignant and difficult-to-treat solid and blood tumors. The development of specific drugs against their targets may be a good therapeutic strategy for PBX1-related cancers. Furthermore, we strongly recommend E2A-PBX1 as one of the genes for prenatal screening to reduce the incidence of childhood hematological malignancies.